Influence of Gd Doping on the Structural, Optical, Dielectric, and Magnetic Properties of Znfe2o4: A Combined Experimental and Theoretical Study - Cardenas-Jiron, G (Elsevier Ltd, 2025)
In the present work, gadolinium (Gd) doping on ZnFe2O4 nanoparticles and analysing its structural, optical, dielectric and magnetic properties synthesized via a co-precipitation method. From structural analysis, it confirms that prepared nanoparticles are cubic spinel structure and reduced crystallite size which indicates lattice distortion. The synthesized nanoparticles are spherical shape morphology with agglomerated from FESEM and HR TEM analysis. From SAED pattern confirms that the nanoparticles are polycrystalline in nature and corresponding d-spacing s values are calculated. The optical band gap values are ranging from 1.96 to 2.15 eV with varying Gd concentration, suggesting potential applications in optoelectronics. The elements such as Gd, Zn, Fe and O are presented in the prepared samples confirmed via EDS analysis which ensuring the purity of the samples. Magnetic studies revealed a shift from paramagnetic behavior at lower Gd concentrations to ferro-canting at higher levels, further supported by density functional theory (DFT) calculations, which showed enhanced magnetic moments in Fe atoms due to Gd substitution. Dielectric analysis indicated a decrease in dielectric properties with temperature, though a slight increase is observed with increased Gd concentration. These findings suggest that Gd-doped ZnFe₂O₄ nanoparticles possess tunable properties, making them promising candidates for applications in energy, environmental, and advanced magnetic technologies. © 2024 Elsevier Ltd and Techna Group S.r.l.